Micromorphology and anatomy of the flower of Zephyranthes candida (Amaryllidaceae) - O. S. Fishchuk (Regulatory Mechanisms in Biosystems, 2021)
The use of morphological features of flowers in the taxonomy of plants is becoming increasingly important. The structure of the Zephyranthes candida (Lindl.) Herb. flowers on permanent cross-sectional and longitudinal sections was studied using a light microscope. The genus Zephyranthes belongs to the subtribe Hippeastrinae Walp. tribe Hippeastreae Sweet., family Amaryllidaceae s.l. Microscopic studies of the flower are considered as a tool to identify hitherto unknown structural adaptations of plants to specialized pollination methods and to elucidate the first stages of fruit morphogenesis, as many features of the fruit appear at the flower stage. The morphometric parameters, morphology, anatomy, and vascular anatomy of the ovary were described by using the flower’s transverse sections. Ten flowers of Z. candida were sectioned using standard methods of Paraplast embedding and serial sectioning at 20 μm thickness. Sections were stained with Safranin and Astra Blau and mounted in Eukitt. It was found that in the studied species the tepals have multi-bundle traces of 10–12 leading bundles. We consider the gynoecium of the studied species to be eusincarpous. The vascular system of the inferior ovary consists of three dorsal and three septal bundles, paired ventral bundles of carpels, which form ovule traces. For the first time, the presence of the following gynoecium zones was detected: a synascidiate structural zone with a height of about 360 μm and a fertile symplicate structural zone with a height of about 1560 μm and a hemisymplicate zone of 480 μm. Septal nectaries appear in the hemisymplicate zone and open with nectary split at the base of the style, the total height of the septal nectary is 760 μm. The ovary roof is 280 μm. Bifurcated dorsal and septal bundles of carpels have been identified, which can be considered as adaptations of the early stages of fruit morphogenesis to opening. Anatomical features of the ovary of Z. candida are numerous vascular bundles in the pericarpium, non-lignified endocarp at the flower stage, we consider as adaptations to the formation of juicy fruit. New data on the anatomical structure of the flower are a significant addition to the information on antecological and post-anthetic features of the studied species. Also, these data can be used in the construction of parsimony branches of the family Amaryllidaceae.